2021
DOI: 10.1115/1.4049958
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Fluid Dynamics Investigation of Pneumatic Atomization, Aerosol Transport, and Deposition in Aerosol Jet Printing Process

Abstract: Aerosol jet printing (AJP) is a direct-write additive manufacturing technique, which has emerged as a high-resolution method for the fabrication of a broad spectrum of electronic devices. Despite the advantages and critical applications of AJP in the printed-electronics industry, the AJP process is intrinsically unstable, complex, and prone to unexpected gradual drifts, which adversely affect the morphology and consequently the functional performance of a printed electronic device. Therefore, in situ process m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 50 publications
(87 reference statements)
0
13
0
Order By: Relevance
“…As a result, a stronger Saffman lift force pointing to the channel center was induced in the converging channel, which enhanced the lateral migration of the aerosol particle and led to a smaller focusing bandwidth. Figure 6 D,E shows that the lateral migration of the aerosol particle was further enhanced by the reverse external force, and the particle focusing bandwidth was ~8 μm, which is much smaller than the bandwidth achieved by the existing focusing methods [ 12 , 19 , 34 ] and commercial aerosol jet printing. The best focusing of the aerosol particle could be obtained by combining the converging geometry and the reverse external force, both of which increased the velocity difference between the aerosol particle and the gas.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…As a result, a stronger Saffman lift force pointing to the channel center was induced in the converging channel, which enhanced the lateral migration of the aerosol particle and led to a smaller focusing bandwidth. Figure 6 D,E shows that the lateral migration of the aerosol particle was further enhanced by the reverse external force, and the particle focusing bandwidth was ~8 μm, which is much smaller than the bandwidth achieved by the existing focusing methods [ 12 , 19 , 34 ] and commercial aerosol jet printing. The best focusing of the aerosol particle could be obtained by combining the converging geometry and the reverse external force, both of which increased the velocity difference between the aerosol particle and the gas.…”
Section: Resultsmentioning
confidence: 89%
“…The focusing performance of aerosol particles in the nozzle strongly depend on the flow conditions and the channel geometry [ 10 ]. Although these passive methods have the advantages of simple structure and easy operation, harsh flow conditions are often required to induce sufficient aerodynamic force [ 11 , 12 ]. For example, a gas velocity higher than 100 m/s is often needed for the focusing of the aerosol particles in the converging nozzle [ 3 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to select nanoparticle functional ink with high boiling point and high viscosity co-solvent for aerosol jet printing, which helps obtain printed lines with good edge definition by reducing the coffee ring effect. Moreover, due to the equipped ultrasonic atomizer, the range of viscosity for the adopted functional ink is limited 23 . On the other hand, it is essential to adopt single-walled CNTs with a low number of wall defects, otherwise the defect can cause deformation of the CNTs along the tube axis, which could be problematic during aerosol transportation.…”
Section: Experiments and Methodsmentioning
confidence: 99%
“…It was observed that the transport of molten PCL through the micro-capillary nozzle (under a flow pressure of 550 kPa) would be a viscous flow having a Reynolds number ( Re ) of 1  , implied from Figure 4(c). This PME material deposition regime is unlike that of the other additive manufacturing processes, such as AJP, where material deposition is intrinsically turbulent [14,16,17].…”
Section: Am Processes For Bone Tissue Engineering 21 Pneumatic Micro-...mentioning
confidence: 99%